Use of a Reverse Bohlman Technique for Low-Grade Spondylolisthesis - PHAM, MARTIN H. (Int J Spine Surg, 2019)
BACKGROUND: Treatment of spondylolisthesis can be difficult with regard to patients with high sacral slopes that may prohibit placement of interbody grafts for fusions across that segment. Here, we describe placement of a reverse Bohlman technique from an anterior approach to obtain fusion across a low-grade spondylolisthesis with a high sacral slope to obtain anterior fusion. METHODS: A chart review was conducted on this single patient regarding his clinical course and outcome. RESULTS: A 54-year-old male presented with low-back pain associated with bilateral leg pain dating back several years. Plain films demonstrated a Grade II isthmic spondylolisthesis at L5–S1 with spinopelvic measurements of 73° sacral slope, 82° lumbar lordosis, 12° pelvic tilt, and 94° pelvic incidence. Magnetic resonance imaging showed bilateral L5 pars defects with diffuse degenerative disease from L4 through S1 and significant ligamentous and facet hypertrophy. He underwent an L4–5 anterior lumbar interbody fusion and an L5–S1 reverse Bohlman placement of a transvertebral transsacral titanium mesh cage. This was supplemented with a posterior decompression and instrumentation from L4-ilium. He had resolution of his radiculopathy and has maintained a good clinical outcome at 3 years follow up. CONCLUSIONS: We present here a patient with low-grade spondylolisthesis and a steep sacral slope who underwent a successful reverse Bohlman approach with long-term follow up. This report highlights the potential utility of this method as a viable alternative for patients with low-grade spondylolisthesis. LEVEL OF EVIDENCE: IV. CLINICAL RELEVANCE: Technical description of surgical technique.